SEXUALITY AND THE CATHOLIC PRIESTHOOD the 'chaste' caste. - Marzano, Marco (ROUTLEDGE, 2025)
Based on interviews with Roman Catholic seminarians, priests and former priests, as well as with managers of seminaries, teaching staff, psychologists and psychiatrists, this book considers the lives of the clergy, beginning with the period before entering the seminary. With attention to both heterosexual and homosexual relationships - and so addressing the tension that exists between Catholic teaching and the reality of clerical lives - this wide-ranging description of seminary life encompasses many issues which are not strictly sexual or emotional, such as time organisation, the importance of study, hierarchical relations and friendship. Showing that the lives of seminarians - and later, priests - are absorbed in balancing the expectations of their role with their need for an emotional life and with maintaining an independent, free inner self, with the result that celibacy can come to be viewed as a pretence to be upheld scrupulously in the public sphere only, Sexuality and the Catholic Priesthood: The 'Chaste' Caste will appeal to scholars of sociology and religious studies with interests in gender and sexuality, the Catholic Church and priestly vocations.
Keywords: Catholic Church -- Clergy -- Sexual behavior.; Celibacy -- Catholic Church.; Sexual abstinence -- Religious aspects -- Catholic Church.; elektronické knihy; electronic books